Ciliary neurotrophic factor improves diabetic parameters and hepatic steatosis and increases basal metabolic rate in db/db mice - Sleeman, M. W. (National Academy of Sciences, 2003)
Obesity plays a central role in the development of insulin resistance and type 2 diabetes. We therefore examined the effects of a modified form of ciliary neurotrophic factor [Axokine, which is hereafter referred to as ciliary neurotrophic factor (CNTF)(Ax15)], which uses a leptin-like mechanism to reduce body weight, in the db/db murine model of type 2 diabetes. In previous studies, weight loss produced by CNTF treatment could largely be attributed to its effects on food intake. In contrast, CNTF(Ax15) treatment of db/db mice caused significantly greater weight loss and marked improvements in diabetic parameters (e.g., levels of glucose, insulin, triglyceride, cholesterol, and nonesterified free fatty acids) than could be accounted for by reduced caloric intake alone. These beneficial effects, above and beyond those seen in animals controlled for either food restriction or body weight, correlated with the ability of CNTF(Ax15) to increase metabolic rate and energy expenditure and reduce hepatic steatosis while enhancing hepatic responsiveness to insulin. The hepatic effects were linked to rapid alterations in hepatic gene expression, most notably reduced expression of stearoyl-CoA desaturase 1, a rate-limiting enzyme in the synthesis of complex lipids that is also markedly suppressed by leptin in ob/ob mice. These observations further link the mechanisms of CNTF and leptin action, and they suggest important, beneficial effects for CNTF in diabetes that may be distinct from its ability to decrease food intake; instead, these effects may be more related to its influence on energy expenditure and hepatic gene expression.